2014
DOI: 10.1038/nature13278
|View full text |Cite
|
Sign up to set email alerts
|

The poleward migration of the location of tropical cyclone maximum intensity

Abstract: , 2014: The poleward migration of the location of tropical cyclone maximum intensity. Nature, 509, 349-352.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
476
6
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 594 publications
(540 citation statements)
references
References 30 publications
57
476
6
1
Order By: Relevance
“…Recently, Kossin et al [2014] identified a pronounced poleward migration in the average latitude of the global mean TC lifetime maximum intensity from the global historical records over the past 30 years. They argued that the migration away from the tropics is linked to changes in the mean meridional structure of environmental vertical wind shear and potential intensity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kossin et al [2014] identified a pronounced poleward migration in the average latitude of the global mean TC lifetime maximum intensity from the global historical records over the past 30 years. They argued that the migration away from the tropics is linked to changes in the mean meridional structure of environmental vertical wind shear and potential intensity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the deepest societal concerns about the consequence of global warming is how TC activity has changed or will change in this region. Considerable effort has been made to understand the response of TC activity to global warming, but so far relatively few studies have been conducted on possible changes in the mean TC genesis location and impact area [Knutson et al, 2010;Seneviratne et al, 2012;Christensen et al, 2013;Kossin et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes potentially increase the expected magnitude of the flood hazard as well as the uncertainty associated with projecting the hazard, yet changes in tropical cyclone intensity and frequency are also spatially variable. For example, Kossin et al [47] showed a poleward migration of maximum cyclone intensity over the last 30 years, on the order of 50-60 km/decade. While global occurrence of tropical cyclones is expected to decrease in the future-modeling studies yield decreases in frequency in the range of 6 to 34 % globally by 2100 [44]-there is a wide variation in regional cyclone frequency projections (e.g., [4,45,84,85]).…”
Section: Nonstationary Considerations-decadal Variability and Long-tementioning
confidence: 99%
“…Langenberg [Langenberg et al, 1999] found that there is an increasing tendency in extreme sea level events induced by winter storms in coasts in the North Sea and related it to changes in climate which may be enhanced by global warming. The fact that global warming also enhances the migration of tropical cyclones toward higher latitudes (Kossin et al 2001) suggests possible modifications in the frequency of intensified storms over the world regardless of the season. In fact, the number of extratropical cyclones over the northern Pacific in winter tends to increase at the rate of 0.21 per year, along with an increase in the induced wind velocity and ocean wave height ( [Graham and Diaz, 2001]).…”
Section: Introductionmentioning
confidence: 99%